Outcomes of surgery in epithelial ovarian cancer: our experience - Lekawale, Hemant S.; Gaidole, Rachana V. (International Surgery Journal, 2019)
Background: Comprehensive surgical staging and surgical cytoreduction is the primary modality of treatment in early and advanced epithelial ovarian cancer respectively, followed by systemic chemotherapy in most of the patients. The aim of the present study was to evaluate the role of surgery and its impact on disease free and overall survival in patients with epithelial ovarian cancer. Methods: A retrospective analysis of 38 patients of biopsy proven epithelial ovarian cancer was performed. Patient’s demographic data, details of surgical procedure, post-operative complications, histopathological findings, staging and pattern of recurrence were collected from the medical records. Results: Six (15.8%) patients had early disease (stage I-II) at presentation while 30 (94.7%) patients advanced disease (stage III-IV). Staging laparotomy was done in six (15.8%) patients, primary cytoreduction in eight (21.05%) patients, interval cytoreduction in 17 (81.6%) patients and secondary cytoreduction in two (5.3%) patients. Five (13.2%) patients were inoperable. The median follow up time was in the range of 2 to 56 months (median 26 months). The three years overall survival in advanced stage was 73.74%. Disease free survivals in primary and interval cytoreduction groups were 80% and 58.67% respectively. The disease free survival in patients with optimal cytoreduction was 72.9%. Conclusions: The present study indicates that in the majority of patients with advanced ovarian cancer, surgery can lead to optimal cytoreduction with acceptable disease-free and overall survival.